2004
DOI: 10.1001/archopht.122.8.1141
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance and Course of Retinopathy in Children WithSevere Malaria

Abstract: Objectives: To relate retinal findings in children treated for severe malaria to disease outcome and to determine the course of changes in the fundus. Methods: A prospective study of children with cerebral malaria (CM) and severe malarial anemia admitted to the Malaria Research Project, Blantyre, Malawi, during 2 malaria seasons. Indirect and direct ophthalmoscopy were performed on admission and daily, subject to the patient's cooperation. Results: Threehundredtwenty-sixpatients(91%)withcomplicated malaria wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
162
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(181 citation statements)
references
References 23 publications
16
162
3
Order By: Relevance
“…Children were eligible for the cerebral malaria group if they met the following inclusion criteria: an age of 0.5-12 years; a Blantyre coma score (BCS) of ≤2 on admission; detection of P. falciparum on a blood smear; no evidence of meningitis; no improvement in the BCS after correction of hypoglycemia (if present); and fundoscopy-based detection of retinopathy (defined as whitening, hemorrhage, or vessel changes) by a trained clinician within 6 hours of admission [13]. Exclusion criteria included gross signs of malnutrition, head trauma, preexisting brain injury, clinical manifestations of advanced AIDS or human immunodeficiency virus infection, or achievement of a BCS of >2 within 4 hours of admission.…”
Section: Human Participation Ethics Statementmentioning
confidence: 99%
“…Children were eligible for the cerebral malaria group if they met the following inclusion criteria: an age of 0.5-12 years; a Blantyre coma score (BCS) of ≤2 on admission; detection of P. falciparum on a blood smear; no evidence of meningitis; no improvement in the BCS after correction of hypoglycemia (if present); and fundoscopy-based detection of retinopathy (defined as whitening, hemorrhage, or vessel changes) by a trained clinician within 6 hours of admission [13]. Exclusion criteria included gross signs of malnutrition, head trauma, preexisting brain injury, clinical manifestations of advanced AIDS or human immunodeficiency virus infection, or achievement of a BCS of >2 within 4 hours of admission.…”
Section: Human Participation Ethics Statementmentioning
confidence: 99%
“…Almost all children with CM who have lumbar puncture have elevated cerebrospinal fluid (CSF) opening pressure 1,2 but only 10-15% have papilledema. 3,4 ICP monitoring in 23 Kenyan children with CM found that all had raised ICP 5 and that single lumbar puncture pressure measurements did not predict the maximum ICP. Several children in that study developed severe intracranial hypertension, all of whom subsequently died or had neurological sequelae.…”
Section: Introductionmentioning
confidence: 98%
“…Retinal hemorrhages in these patients usually absorbed spontaneously over the period of one to four weeks without retinal sequelae [9] and visual defect improved completely after successful treatment of malaria. Few cases have been reported with irreversible visual defects [7].…”
Section: Discussionmentioning
confidence: 91%
“…Among these four changes, retinal whitening and vessel changes are specific and diagnostic of severe malarial disease [8]. The incidence of retinal haemorrhages was found in 46% cases of cerebral malaria [9]. This incidence was around 60% in children with cerebral malaria and was lower in less severe malarial disease [2].…”
Section: Discussionmentioning
confidence: 99%